2016
DOI: 10.5194/amt-9-509-2016
|View full text |Cite
|
Sign up to set email alerts
|

A dual-inlet, single detector relaxed eddy accumulation system for long-term measurement of mercury flux

Abstract: Abstract. The fate of anthropogenic emissions of mercury (Hg) to the atmosphere is influenced by the exchange of elemental Hg with the earth surface. This exchange holds the key to a better understanding of Hg cycling from local to global scales, which has been difficult to quantify. To advance research about land–atmosphere Hg interactions, we developed a dual-inlet, single detector relaxed eddy accumulation (REA) system. REA is an established technique for measuring turbulent fluxes of trace gases and aeroso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 79 publications
(91 reference statements)
1
43
1
Order By: Relevance
“…The REA method has been deployed for flux measurements for agricultural lands, forest canopies, wetlands and urban settings (Cobos et al, 2002;Olofsson et al, 2005;Bash and Miller, 2009;Osterwalder et al, 2016;Sommar et al, 2013b). The AGM method has been used over grasslands, agricultural lands, salt marshes, landfills and snow (Lee et al, 2000;Kim et al, , 2003Fritsche et al, 2008b, c;Baya and Van Heyst, 2010).…”
Section: Micrometeorological Methodsmentioning
confidence: 99%
“…The REA method has been deployed for flux measurements for agricultural lands, forest canopies, wetlands and urban settings (Cobos et al, 2002;Olofsson et al, 2005;Bash and Miller, 2009;Osterwalder et al, 2016;Sommar et al, 2013b). The AGM method has been used over grasslands, agricultural lands, salt marshes, landfills and snow (Lee et al, 2000;Kim et al, , 2003Fritsche et al, 2008b, c;Baya and Van Heyst, 2010).…”
Section: Micrometeorological Methodsmentioning
confidence: 99%
“…Phys. Discuss., https://doi.org /10.5194/acp-2017- (Osterwalder et al, 2016). Furthermore, Osterwalder et al (2016) found significant difference between GEM fluxes during unstable, stable, and neutral conditions with a near-zero flux during stable conditions, emission during unstable conditions and deposition during neutral conditions.…”
Section: Introductionmentioning
confidence: 82%
“…The sampling inlets are located 5.69 m above ground. Osterwalder et al (2016) and Zhu et al (2015b) describe the advantages of using dual inlets, where temporally synchronous concentration determination of updrafts and downdrafts is the most obvious advantage. The Teflon tubes were heated to 50°C and each tube is connected 30 to a three-way valve, which can either collect sample air or zero air.…”
Section: Measurement Of Gem Fluxmentioning
confidence: 99%
See 2 more Smart Citations